(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Elder women often suffer from chest pain and pressure discomfort due to breast displacement during exercise. To design functional sports bras that will mitigate chest pain and pressure discomfort under dynamic conditions, a survey was completed to find out the bra design special requirements and simulation experiments were carried out to investigate breast displacement rules. A standard sized running woman was selected as a subject to determine the typical breast movement positions, and an elder woman avatar was used to simulate the breast displacement. The results showed that by dividing the bra into different functional areas, the breast movement postures can be generated on the virtual model and this method could be applied to develop ergonomic sports bras that can limit the breast movement for elder females. Approaches involved in this research are also suitable to design sportswear with specific functional requirements for various age women.